The Value of Study Abroad beyond Labor Market Benefits - Mihut, Georgiana (International Higher Education, 2025)
<h3 id="when-students-cross-borders-to-study-they-gather-a-deeper-understanding-of-different-people-and-contribute-to-the-public-good-however-the-value-of-study-abroad-is-often-justified-not-on-the-grounds-of-tolerance-but-because-it-brings-labor-market-benefits-a-dilemma-emerges-because-studies-increasingly-show-fewer-labor-market-benefits-for-study-abroad-participants-this-raises-questions-about-how-we-judge-promote-and-foster-the-value-of-study-abroad-and-about-the-related-research-agenda" data-pm-slice="1 1 []">When students cross borders to study, they gather a deeper understanding of different people and contribute to the public good. However, the value of study abroad is often justified not on the grounds of tolerance, but because it brings labor market benefits. A dilemma emerges because studies increasingly show fewer labor market benefits for study abroad participants. This raises questions about how we judge, promote, and foster the value of study abroad and about the related research agenda.